BandBlock: Bandwidth allocation in blockchain‐empowered UAV‐based heterogeneous networks - Venkateswarararao, Kuna; Kumar, Pratik; Solanki, Akash; Swain, Pravati (ETRI journal, 2022)
The 5G mobile network is promising to handle the dynamic traffic demands of user equipment (UE). Unmanned aerial vehicles (UAVs) equipped with wireless transceivers can act as flying base stations in heterogeneous networks to ensure the quality of service of UE. However, it is challenging to efficiently allocate limited bandwidth to UE due to dynamic traffic demands and low network coverage. In this study, a blockchain‐enabled bandwidth allocation framework is proposed for secure bandwidth trading. Furthermore, the proposed framework is based on the Cournot oligopoly game theoretical model to provide the optimal solution; that is, bandwidth is allocated to different UE based on the available bandwidth at UAV‐assisted‐based stations (UBSs) with optimal profit. The Cournot oligopoly game is performed between UBSs and cellular base stations (CBSs). Utility functions for both UBSs and CBSs are introduced on the basis of the available bandwidth, total demand of CSBs, and cost of providing cellular services. The proposed framework prevents security attacks and maximizes the utility functions of UBSs and CBSs.